Nilai-Nilai Cinta Kasih dalam Film Layar Lebar âRindu Kami PadaMuâ - Anggitya, Paramastu titis (KOMUNITAS, 2015)
ByÂ  nature,Â  everyÂ  humanÂ  beingÂ  endowedÂ  theÂ  feelingsÂ  ofÂ  loveÂ  inÂ  differentÂ  levels,Â  thatÂ  affects behaviorÂ  andÂ  viewÂ  ofÂ  loveÂ  valuesÂ  differences.Â  TheÂ  fadingÂ  ofÂ  loveÂ  inÂ  humanÂ  beingsÂ  today encourages various efforts to place love compassions in human life. Through a film titled âRindu Kami PadaMuâ, longing of love shown by using certain symbols which is not easily understood byÂ  theÂ  audienceÂ  atÂ  aÂ  glanceÂ  asÂ  effortsÂ  toÂ  placeÂ  loveÂ  compassions.Â  ThisÂ  studyÂ  isÂ  resultÂ  ofÂ  a qualitativeÂ  researchÂ  usingÂ  RolandÂ  BarthesÂ  semioticÂ  analysisÂ  approachÂ  andÂ  RobertÂ  Sternbergâs typology of love theory. The result showed that âRindu Kami PadaMuâ is a film that reflects the longing of love, including love for family, spouse,human beings, God and the environment. This filmÂ  teachesÂ  theÂ  importanceÂ  ofÂ  loveÂ  valuesÂ  placementÂ  inÂ  universalÂ  life.Â  BasedÂ  onÂ  Robert Sternbergâs typology of love theory, it can be seenthat the types of love in this film consist of nonlove,Â  liking,Â  romanticÂ  love,Â  fatuousÂ  love,Â  andÂ  consummateÂ  loveÂ  whichÂ  areÂ  variously experienced by all characters.